Accelerated and high‐resolution cardiac T2 mapping through peripheral k‐space sharing. Issue 1 (29th July 2018) - Darçot, Emeline; Yerly, Jérôme; Colotti, Roberto; Masci, Pier Giorgio; Chaptinel, Jerome; Feliciano, Helene; Bianchi, Veronica; van Heeswijk, Ruud B.
Abstract : Purpose: To develop high‐spatial‐resolution cardiac T2 mapping that allows for a reduced acquisition time while maintaining its precision. We implemented and optimized a new golden‐angle radial T2 mapping technique named SKRATCH (Shared k‐space Radial T2 Characterization of the Heart) that shares k‐space peripheries of T2 ‐weighted images while preserving their contrasts. Methods: Six SKRATCH variants (gradient‐recalled echo and balanced SSFP, free‐breathing and breath‐held, with and without a saturation preparation) were implemented, and their precision was compared with a navigator‐gated reference technique in phantoms and 22 healthy volunteers at 3 T. The optimal breath‐held SKRATCH technique was applied in a small cohort of patients with subacute myocardial infarction. Results: The faster free‐breathing SKRATCH technique reduced the acquisition time by 52.4%, while maintaining the precision and spatial resolution of the reference technique. Similarly, the most precise and robust breath‐held SKRATCH technique demonstrated homogenous T2 values that did not significantly differ from the navigator‐gated reference (T2 = 39.9 ± 3.4 ms versus 39.5 ± 3.4 ms, P > .20, respectively). All infarct patients demonstrated a large T2 elevation in the ischemic regions of the myocardium. Conclusion: The optimized SKRATCH technique enabled the accelerated acquisition of high‐spatial‐resolution T2 maps, was validated in healthy adult volunteers, and was successfully applied to a small initial group of patients.